2015
DOI: 10.1063/1.4919782
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale thermocapillary flow in focused ion beam milling

Abstract: Focused ion beams provide a means of nanometer-scale manufacturing and material processing, which is used for applications such as forming nanometer-scale pores in thin films for DNA sequencing. We investigate such a configuration with Ga + bombardment of a Si thin-film target using molecular dynamics simulation. For a range of ion intensities in a realistic configuration, a recirculating melt region develops, which is seen to flow with a symmetrical pattern, counter to how it would flow were it driven by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Nanometric-scale manufacturing with focused ion beams is also developing fast for applications such as forming nanopores in thin films for DNA sequencing. Atomic-scale thermocapillary flow was demonstrated in this process by means of MD simulations [26].…”
Section: Introductionmentioning
confidence: 99%
“…Nanometric-scale manufacturing with focused ion beams is also developing fast for applications such as forming nanopores in thin films for DNA sequencing. Atomic-scale thermocapillary flow was demonstrated in this process by means of MD simulations [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also shown that such a convective flow may also occur in the micro-scale environment of the applications of manufacturing micro-and nanodevices. The works of Murata and Mochizuki, 2006;Maier et al, 2012;Das et al, 2015a;Das, 2015b have shown that Marangoni convection develops even in the nano-meter scale.…”
Section: Introductionmentioning
confidence: 99%